Класифікація конкурентних стратегій підприємства залежно від впливу на результативність - Краснокутська, Наталія Станіславівна; Фощій, Петро Миколайович (My University, 2018)
У статті досліджено і систематизовано науково-методологічні підходи до поняття "результативність діяльності підприємств". На основі аналізу поняття результативності діяльності було виділено 4 проекції результативності. На основі класифікації основних показників результативності в проекційному погляді в статті представлено класифікацію конкурентних стратегій залежно від очікуваної результативності. У результаті отримано 4 види конкурентних стратегій, які одразу чинять вплив на одні, дві, три чи чотири проекції результативності діяльності підприємства.

The article has been researched and systematized scientific and methodological approaches to the concept of "effectiveness of enterprises". Based on the four main concepts of performance analysis, 4 projections of effectiveness were identified. Based on the classification of the main performance indicators, in the projection view, the article presents the classification of competitive strategies, depending on the expected performance. As a result, we have received 4 types of competitive strategies, which immediately affect the one, two, three or four projections of the company's performance.
Classification of the competitive strategies of the enterprise in dependence on the effect of results
Keywords: конкуренція; проекційний погляд; стратегія диференціації ринку; товари; послуги; competition; competitive strategy; effectiveness; classification of competitive strategy; projection of enterprise activity effectiveness